The effect of protein-energy levels dietary on Kacang goats performances - MuchJi Martawidjaja; B Setiadi; Sorta S Sitorus (Indonesian Center for Animal Research and Development (ICARD), 1999)
An experiment was done to evaluate the protein-energy requirement for growing Kacang goats. Twelve males and 18 female goats, seven to eight months old were used in this study and randomized into three treatment groups, with four and six animals each, and were kept in individual pens. The treatments used were: R1= Elephant grass (E.G.) + concentrate C1 (21% CP; 3.9 Mcal GE/kg), R2 = E.G. + concentrate C2 (17% CP; 3.7 Mcal GE/kg), and R3 = E.G. + concentrate C3 (12% CP; 3.5 Mcal GE/kg), respectively. Fresh Elephant grass was offered in restricted, and concentrate was offered at 3% of body weight. The experiment was carried out for 12 weeks. Data were analysed by using factorial completely randomized design 2x3 (3 rations and 2 sexes). Parameters measured were: feed intake; average daily gain and feed conversion. The results indicated that among treatments there was no significant difference on dry matter (DM) and gross energy (GE) intake (P>0.05), but crude protein (CP) intake of R1 was 23,6% higher than treatment R2; treatment R2 was 38.1% higher than R3 (P<0.01). Average daily gain (ADG) between treatment R1 and R2, and between R2 and R3 were not significantly different (P>0.05), but treatment R1 was 36.9% and significantly higher than R3 (P<0.01). Feed conversion (FC) between R1 and R2, and between R2 and R3 were not significantly different (P>0.05), but ration R1 was more efficient than R3 (P<0.01). DM intake, GE intake, and ADG of male goats each were 19.4% (P<0.05); 19.0% (P<0.01), and 28.2% (P<0.01) significantly higher than the female goats. Feed conversion between male and female goats was not significantly different (P>0.05). It was concluded that protein intake and average daily gain were increased, and feed conversion was more efficient as the crude protein-energy levels increased in the ration. Feed intake and average daily gain of male goats were higher and feed conversion was more efficient than the female goats. Key words : Protein-energy, Kacang goat